2018
DOI: 10.1021/acs.langmuir.8b03233
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Crystallization of Particles at the Air–Water Interface Induced by Minute Amounts of Surfactant

Abstract: Controlling the organization of particles at liquid–gas interfaces usually relies on multiphasic preparations and external applied forces. Here, we show that micromolar amounts of a conventional cationic surfactant induce, in a single step, both adsorption and crystallization of various types of nanometer- to micrometer-sized anionic particles at the air–water interface, without any additional phase involved or external forces other than gravity. Contrary to conventional surfactant-induced particle adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 40 publications
5
43
0
Order By: Relevance
“…After 60 min, the small vessel is brought to its initial position, where the aqueous suspension is the bottom phase and the monolayer of adsorbed particles can be easily visualized with a straight microscope (the method is described in detail in refs. [76,77]). The main advantage of this second method is that it does not require of the application of magnetic field gradients, which may promote the formation of permanent aggregates.…”
Section: Methodsmentioning
confidence: 99%
“…After 60 min, the small vessel is brought to its initial position, where the aqueous suspension is the bottom phase and the monolayer of adsorbed particles can be easily visualized with a straight microscope (the method is described in detail in refs. [76,77]). The main advantage of this second method is that it does not require of the application of magnetic field gradients, which may promote the formation of permanent aggregates.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that micromolar amounts of conventional cationic surfactants (for example, dodecyltrimethylammonium bromide, DTAB) induced the adsorption of anionic particles by decreasing the adsorption barrier at the air/water interface . At such low surfactant concentrations (≈CMC/1000–CMC/100, where CMC is the critical micelle concentration), the particles adsorbed with a low contact angle (≈30°) and remained highly charged, forming disordered assemblies or polycrystalline patches in a particle‐ and surfactant‐concentration‐dependent manner.…”
Section: Figurementioning
confidence: 99%
“…Note that 10 μ m of AzoTAB is about three orders of magnitude lower than its CMC (12.6 m m and 14.6 m m for the trans and cis isomers, respectively), resulting in a surface tension comparable to that of pure water, regardless of irradiation conditions (Supporting Information, Figure S1). The particles were brought to the air/water interface of a suspension in a cylindrical cell by flipping it up and down using our previously described protocol (Figure C, top panel). We found that, similarly to the case of non‐photosensitive surfactants, almost all particles adsorbed at the air/water interface and accumulated at the center of the cylindrical well containing the sample due to the slightly concave shape of the meniscus.…”
Section: Figurementioning
confidence: 99%
“…We recently showed that micromolar amounts of conventional cationic surfactants (for example,dodecyltrimethylammonium bromide,DTAB) induced the adsorption of anionic particles by decreasing the adsorption barrier at the air/water interface. [30] At such low surfactant concentrations (% CMC/ 1000-CMC/100, where CMC is the critical micelle concentration), the particles adsorbed with al ow contact angle ( % 308 8)a nd remained highly charged, forming disordered assemblies or polycrystalline patches in ap article-and surfactant-concentration-dependent manner.H ere,t o explore the possibility to dynamically switch particle assemblies at the air/water interface at constant composition, we used anionic polystyrene particles (diameter 5.1 mm) at af ixed concentration (0.01 mg mL À1 )a nd 10 mm of the AzoTAB photosensitive surfactant [31][32][33] (Figure 1A). AzoTAB is ac ationic surfactant with an azobenzene moiety in its hydrophobic tail, which can isomerize from trans to cis upon suitable light irradiation ( Figure 1B).…”
mentioning
confidence: 99%
“…Note that 10 mm of AzoTAB is about three orders of magnitude lower than its CMC (12.6 mm and 14.6 mm for the trans and cis isomers, respectively [34] ), resulting in as urface tension comparable to that of pure water, regardless of irradiation conditions (Supporting Information, Figure S1). Thep articles were brought to the air/water interface of as uspension in ac ylindrical cell by flipping it up and down using our previously described protocol [30] ( Figure 1C,t op panel). We found that, similarly to the case of non-photosensitive surfactants,a lmost all particles adsorbed at the air/water interface and accumulated at the center of the cylindrical well containing the sample due to the slightly concave shape of the meniscus.I nt he absence of light irradiation, the particles formed adisordered structure containing voids ( Figure 1C-i).…”
mentioning
confidence: 99%